The structure of the development of motor transport engineers-pedagogues’ professional competence in the system of postgraduate pedagogical education - Hornostaieva, О. (Problems of Engineer-Pedagogical Education, 2020)
The article presents the basic approaches to structuring the professional competence of engineerspedagogues of the motor transport sphere. The author presents her own vision of the structure of professional competence as a complex unity of interconnected components. An attempt is made to optimize the components of professional competence of engineers-pedagogues of the motor transport field. The components (technical, technological, methodological, psychological-pedagogical, special-subject, intellectual-cognitive, communicative, logistic, economic) are characterized, which allows ensuring a successful result and to provide engineers-pedagogues of the motor transport sphere with a high level of knowledge and skills. The article distinguishes motivational-value, gnostic-activity and personality-reflexive criteria of professional competence of engineers-pedagogues in the field of motor transport, and determines the levels of professional competence of engineers-pedagogues in the field of motor transport, namely initial (reconstructive), sufficient (variational), and high (creative). The papers highlights pedagogical conditions for the development of professional competence of engineers-pedagogues, such as updating the content of advanced training and internship, participating in workshops and professional trainings, improving methodological competence, mastering information and telecommunication technologies, participating in conferences and scientific activities. Special attention is paid to the stages of the development of professional competence of engineerspedagogues in the field of motor transport, which are implemented at institutions of advanced training and postgraduate education, educational-methodological offices (centers), vocational education institutions specializing in motor transport, in the process of self-education, at enterprises. The author suggests a newly designed model for the development of professional competence of engineers-pedagogues in the process of advanced training. The proposed model for the development of professional competence of engineers-pedagogues of the motor transport field in the process of advanced training can be applied in the system of postgraduate pedagogical education.